Finding the root cause: Embedding vegetable education into pre-health professional programs using an iterative mixed-methods approach - Smith, Felicity; Phelps, Charlotte; Moro, Christian (Journal of University Teaching and Learning Practice, 2025)
Reduced consumption of fruits and vegetables is linked to an increased risk of noncommunicable diseases and chronic health issues. With health professionals at the frontline of patient care, there has been an identified need to enhance vegetable education throughout training programs. In undertaking this curriculum change, Design-Based Research (DBR) presents a modern framework highly suitable for health professional programs due to its focus on co-development with a variety of stakeholders. This study aimed to utilise a DBR approach to develop insights and recommendations into what would constitute an effective and evidence-based vegetable curriculum that can be embedded within a pre-health professional course. This study underwent a five-phase iterative process of DBR with a mixed-methods research approach used to collect both quantitative and qualitative data to explore stakeholders’ perceptions. The results provide three evidence-based recommendations for educators and curriculum developers to assist in the creation and embedding of vegetable education into a pre-health professional curriculum. Firstly, this study highlights that any resource or curriculum change should be simple, focussing on reiterating the regional government’s recommended intake of vegetables and fruits. Moreover, any resource should involve hands-on activities such as laboratories or workshops and be embedded directly into the curriculum rather than self-study options. With the five phases, DBR provides an ideal framework for educational research due to its iterative design and the engagement of stakeholders.